Lexical Density and Politeness Strategies in EFL Writings - Ghada Haji (Yayasan Visi Intan Permata, 2024)
This study adopts a corpus-based analytical approach to assess lexical density and politeness strategies performance in the writings of English as a Foreign Language (EFL) graduate students. The data consists of 30 job application letters produced by university students enrolled in Master One, IT Management. AntConc tool was used to compute the lexical density relying on Ure’s (1971) method. Besides, Brown and Levinson’s (1987) coding scheme of politeness was employed to trace the pragmatic strategies used by non-native English speakers in the target language. The findings revealed that the participants’ letters are commonly categorized as Not Dense, indicating a low language proficiency. As for the performance of politeness strategies, the results suggest that students lacked awareness regarding the use of some necessary positive and negative strategies and insufficient attention has been paid to the pragmatic aspect of their texts. The linguistic and pedagogical implications of this paper will be significantly pertinent to EFL and ESL academic writing instructors, curriculum designers, and language teaching researchers.